Clinical outcomes following pre-, pro- and synbiotic supplementation after caesarean birth or antibiotic exposure in the first week of life in term born infants: A systematic review of the literature - Kamphorst, Kim; Carpay, Nora C.; de Meij, Tim G. J.; Daams, Joost G.; van Elburg, Ruurd M.; Vlieger, Arine M. (Frontiers in Pediatrics, 2022)
Background: Caesarean section and early exposure to antibiotics disrupt the developing gastrointestinal microbiome, which is associated with long-term health effects. Objective: The aim of this systematic review was to summarise the impact of prebiotics, probiotics, or synbiotics supplementation on clinical health outcomes of term infants born by caesarean section or exposed to antibiotics in the first week of life. Design: A systematic search was performed in Medline and Embase from inception to August 2021. Title and abstract screening (n=11,248), full text screening (n=48), and quality assessment were performed independently by two researchers. Results: Six RCTs studying caesarean born infants were included, group sizes varied between 32-193 with in total 752 children. No studies regarding supplementation after neonatal antibiotic exposure were found. Three studies administered a probiotic, one a prebiotic, one a synbiotic, and one study investigated a prebiotic and synbiotic. . Several significant effects were reported at follow-up varying between 10 days and 13 years: a decrease in atopic diseases (n=2 studies), higher immune response to tetanus and polio vaccinations (n=2), lower response to influenza vaccination (n=1), fewer infectious diseases (n=2), and less infantile colic (n=1), although results were inconsistent. Conclusions: Supplementation of caesarean-born infants with prebiotics, probiotics, or synbiotics resulted in significant improvements in some health outcomes as well as vaccination responses. Due to the variety of studied products and the paucity of studies, no recommendations can be given yet on the routine application of prebiotics, probiotics, or synbiotics to improve health outcomes after caesarean section or neonatal antibiotic exposure.